2024
DOI: 10.1093/jambio/lxae040
|View full text |Cite
|
Sign up to set email alerts
|

Genome-guided purification of high amounts of the siderophore ornibactin and detection of potentially novel burkholdine derivatives produced by Burkholderia catarinensis 89T

Evelise Bach,
Julia Chen,
Célio Fernando Figueiredo Angolini
et al.

Abstract: Aim The increased availability of genome sequences has enabled the development of valuable tools for the prediction and identification of bacterial natural products. Burkholderia catarinensis 89T produces siderophores and an unknown potent antifungal metabolite. The aim of this work was to identify and purify natural products of B. catarinensis 89T through a genome-guided approach. Materials and methods The analysis of B. cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…PlantiSMASH, a branch of antiSMASH, incorporates plant-specific functionality, including plant-adapted hidden Markov model profiles and cluster detection logic, and supports coexpression analysis . An interesting study reported the genome-guided purification of high amounts of the siderophore ornibactin and the detection of potentially novel burkholdine derivatives produced by Burkholderia catarinensis 89T . In that study, the authors, by using genome-guided purification protocols followed by mass spectrometry techniques, were able to detect masses related to putative new derivatives of the siderophore ornibactin and the antifungal burkholdine as well as homoserine lactones probably related to their regulation .…”
Section: Genomic Approach and Bioinformatic Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…PlantiSMASH, a branch of antiSMASH, incorporates plant-specific functionality, including plant-adapted hidden Markov model profiles and cluster detection logic, and supports coexpression analysis . An interesting study reported the genome-guided purification of high amounts of the siderophore ornibactin and the detection of potentially novel burkholdine derivatives produced by Burkholderia catarinensis 89T . In that study, the authors, by using genome-guided purification protocols followed by mass spectrometry techniques, were able to detect masses related to putative new derivatives of the siderophore ornibactin and the antifungal burkholdine as well as homoserine lactones probably related to their regulation .…”
Section: Genomic Approach and Bioinformatic Toolsmentioning
confidence: 99%
“… 122 An interesting study reported the genome-guided purification of high amounts of the siderophore ornibactin and the detection of potentially novel burkholdine derivatives produced by Burkholderia catarinensis 89T. 126 In that study, the authors, by using genome-guided purification protocols followed by mass spectrometry techniques, were able to detect masses related to putative new derivatives of the siderophore ornibactin and the antifungal burkholdine as well as homoserine lactones probably related to their regulation. 126 The antiSMASH technology was used for the characterization of siderophores from E. coli to find the secondary metabolites that cause pathogenicity in urinary tract infections (UTIs).…”
Section: Genomic Approach and Bioinformatic Toolsmentioning
confidence: 99%
See 1 more Smart Citation